WACANA DAN REPRESENTASI SEBAGAI KONSTRUKSI IDEOLOGI DALAM STRIP KOMIK MICE CARTOON INDONESIA BANGET 2! - Ardia Septi Wijianti (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2021)
This study aims to understand the representation in discourse and how discourse constructs ideology in the comic strip Mice Cartoon Indonesia Banget! 2. To understand these two things, representation and social semiotics theories are needed. Both theories are applied to data in the form of visual and verbal language in comic strips. The data in the form of visual and verbal language are categorized based on the anatomy of discourse in social semiotics. The results of the study show that the discourse of Indonesians which is repeated in comic strips represents actors as metonymy of Indonesians which are considered negative. The categorization is based on an analysis of the anatomy of discourse in comic strips in the form of actors, actions, attitudes that are considered deviant and not in accordance with the discourse of people's lives. “Indonesian people” in comic strips are representations of discourses that live in society. The categorization has references that come from social reality in the form of various articles published as a form of discourse legitimacy in comic strips. Although the discourse of Indonesians is seen as a negative representation, this assumption becomes knowledge in comic strips that is taken for granted by readers. In the end, discourse and representation in comic strips are not questioned again. All discourses culminate in ideological construction which is reflected in the title